Angiogenesis inhibitors for small cell lung cancer - Song, Sang-Yun; Park, Cheol-Kyu; Oh, In-Jae; Kim, Young-Chul (Translational Cancer Research; Vol 6, Supplement 3 (May 26, 2017): Translational Cancer Research, 2017)
Small-cell lung cancer (SCLC) accounts for approximately 12–15% of all lung cancers and is characterized by a rapid growth rate and metastasis at the time of diagnosis. Despite its initial sensitivity to first-line chemotherapy, rapid acquisition of resistance to subsequent lines of therapy is usually observed. Although there is a plethora of new drugs being developed for non-small cell lung cancer (NSCLC), there is still a shortage of treatment regimens other than the combination therapy containing platinum and etoposide or irinotecan.